Elimination of inter-domain interactions increases the cleavage fidelity of the restriction endonuclease DraIII. Issue 5 (15th April 2014) - Zhuo, Wei; Lai, Xuhui; Zhang, Liqing; Chan, Siu-Hong; Li, Fengjuan; Zhu, Zhenyu; Yang, Maojun; Sun, Dapeng
Abstract: Dra III is a type IIP restriction endonucleases (REases) that recognizes and creates a double strand break within the gapped palindromic sequence CAC↑NNN↓GTG of double-stranded DNA (↑ indicates nicking on the bottom strand; ↓ indicates nicking on the top strand). However, wild type Dra III shows significant star activity. In this study, it was found that the prominent star site is CAT↑GTT↓GTG, consisting of a star 5′ half (CAT) and a canonical 3′ half (GTG). Dra III nicks the 3′ canonical half site at a faster rate than the 5′ star half site, in contrast to the similar rate with the canonical full site. The crystal structure of the Dra III protein was solved. It indicated, as supported by mutagenesis, that Dra III possesses a ββα-metal HNH active site. The structure revealed extensive intra-molecular interactions between the N-terminal domain and the C-terminal domain containing the HNH active site. Disruptions of these interactions through site-directed mutagenesis drastically increased cleavage fidelity. The understanding of fidelity mechanisms will enable generation of high fidelity REases.